A new species of Tridax (Compositae-Heliantheae) from Durango, Mexico - García Arevalo, Abel (Instituto de Ecología, A.C., 1990)
Tridax durangensis sp. n. is described from the tropical deciduous forest of southern Durango state. The species is related to T. erecta, known from Chihuahua.